Politik dan Kebijakan Pendidikan Islam di Indonesia - Yudi Agung Franata; Andi Zainal Abidin; Kasful Anwar US; Sya'roni Sya'roni (Jurnal Budi Pekerti Agama Islam, 2024)
This study focuses on discussing the politics and policy of Islamic education in Indonesia with the core of the discussion of Comparison of Educational Goals and Systems between Islamic Education and Dutch Colonial Government Education. The history of Islamic education in Indonesia is more or less influenced by the socio-political background, especially during the Dutch colonial era, which was the longest surviving colonizer in Indonesia, this caused damage to the Islamic order that existed in Indonesia at that time, because the Dutch colonialists had a dual mission including Imperialism (a nation that carried out the politics of colonizing other nations) and Christianization. The educational process that took place in the Dutch East Indies was one of the starting points for the emergence of national awakening figures. Education in the Dutch East Indies itself began because of criticism from several figures and groups with the application of forced cultivation and liberal politics, because this policy caused a lot of suffering and poverty of the people. And this must be paid for by organizing trias, namely irrigation, emigration, and education. This criticism was finally approved by the queen of the Netherlands, and education began to be held, but education ran with discrimination because there were schools that differentiated classes between the children of elite nobles or pro-Dutch figures and the children of ordinary people. And this is because the son of this nobleman or pro-Dutch figure will later work to help the Dutch. And the children of ordinary people only become menial or lowly laborers.